Salt-Tolerant Antifungal and Antibacterial Activities of the Corn Defensin ZmD32 - Kerenga, Bomai K.; McKenna, James A.; Harvey, Peta J.; Quimbar, Pedro; Garcia-Ceron, Donovan; Lay, Fung T.; Phan, Thanh Kha; Veneer, Prem K.; Vasa, Shaily; Parisi, Kathy; Shafee, Thomas M. A.; van der Weerden, Nicole L.; et al. (Frontiers in Microbiology, 2019)
Pathogenic microbes are developing resistance to established antibiotics, making the development of novel antimicrobial molecules paramount. One major resource for discovery of antimicrobials is the arsenal of innate immunity molecules that are part of the first line of pathogen defense in many organisms. Gene encoded cationic antimicrobial peptides are a major constituent of innate immune arsenals. Many of these peptides exhibit potent antimicrobial activity in vitro. However, a major hurdle that has impeded their development for use in the clinic is the loss of activity at physiological salt concentrations, attributed to weakening of the electrostatic interactions between the cationic peptide and anionic surfaces of the microbial cells in the presence of salt. Using plant defensins we have investigated the relationship between the charge of an antimicrobial peptide and its activity in media with elevated salt concentrations. Plant defensins are a large class of antifungal peptides that have remarkable stability at extremes of pH and temperature as well as resistance to protease digestion. A search of a database of over 1200 plant defensins identified ZmD32, a defensin from Zea mays, with a predicted charge of +10.1 at pH 7, the highest of any defensin in the database. Recombinant ZmD32 retained activity against a range of fungal species in media containing elevated concentrations of salt. In addition, ZmD32 was active against Candida albicans biofilms as well as both Gram negative and Gram-positive bacteria. This broad spectrum antimicrobial activity, combined with a low toxicity on human cells make ZmD32 an attractive lead for development of future antimicrobial molecules.